A Multifunctional Carbohydrazide‐Based Chromofluorescent Sensor for the Selective Detection of Cu(II) and Zn(II) Ion. Issue 35 (12th December 2017) - Swami, Suman; Agarwala, Arunava; Verma, Ved Prakash; Shrivastava, Rahul
Abstract: A series of multifunctional carbohydrazide based chromofluorescent sensor molecules derived from carbohydrazide, 4‐formyl‐1‐substituted phenyl‐pyrazole‐3‐carboxylate and 2‐hydroxy‐naphthaldehyde were successfully designed and synthesized. The synthesized sensor molecules exhibit significant red shift in their absorption spectra with visual color changes on interaction with Cu(II) and Zn(II) ions. In addition, the optimized sensor showed excellent selectivity towards Cu(II) and Zn(II) ions with fluorescence "turn off" and "turn on" modes respectively. Along with this, anion recognition studies were carried out using UV‐visible and fluorescence spectrophotometric titrations which revealed that synthesized sensors also exhibit selective sensing of F −, CH3 COO − and H2 PO4 − ions via H‐bond interaction and subsequent deprotonation to elicit distinct visual color change from light yellow to orange with significant quenching in its emission intensity. Furthermore, the in‐situ prepared sensor‐anion adduct solution exhibited colorimetric "On‐Off" sensing of Cu(II) and Zn(II) ions, which was confirmed through UV‐visible titration experiments. Abstract : A series of carbohydrazide based multifunctional chromofluorescent sensor molecules were synthesized and evaluated for recognition studies. The spectroscopic studies reveal that sensor molecules selectively sense Cu(II) and Zn(II) ions. Moreover, sensor molecules also exhibit selective sensing of F −, CH3 COO − and H2 PO4 − ion via H‐bond interaction. In‐situ prepared sensor‐anion adduct solution exhibited colorimetric "On‐Off" sensing of Cu(II) and Zn(II) ions.